2019
DOI: 10.1002/adfm.201902890
|View full text |Cite
|
Sign up to set email alerts
|

Multibit Optoelectronic Memory in Top‐Floating‐Gated van der Waals Heterostructures

Abstract: Nonvolatile memories based on van der Waals heterostructures have been proved to be promising candidates for next-generation data storage devices. However, little attention has been focused on the structure with separated floating and control gates (the floating gates and control gates distribute at the different side of the channels), which were recently predicted to be capable of further improving device performance. Here, nonvolatile multibit optoelectronic memories are demonstrated using MoS 2 , hexagonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
90
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(93 citation statements)
references
References 42 publications
2
90
1
Order By: Relevance
“…In this situation, the top Cr‐Au flake, h‐BN, MoS 2 serve as floating‐gate, tunneling barrier, and channel, respectively (inset of Figure a shows the optical microscope image). [ 38 ] The corresponding band diagrams used for the interpretation of this memory behavior can be seen from Figure S8 in the Supporting Information. A small hysteresis was observed in I DS – V GS curve (Figure 3a).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…In this situation, the top Cr‐Au flake, h‐BN, MoS 2 serve as floating‐gate, tunneling barrier, and channel, respectively (inset of Figure a shows the optical microscope image). [ 38 ] The corresponding band diagrams used for the interpretation of this memory behavior can be seen from Figure S8 in the Supporting Information. A small hysteresis was observed in I DS – V GS curve (Figure 3a).…”
Section: Figurementioning
confidence: 99%
“…At the same time, it can be noted that the device with such structure might also act as top floating gate memory where the top Cr‐Au flake acts as a floating gate, the CIPS and h‐BN sheets serve as tunneling layer and Si as a control gate. [ 38 ] However, we found that this mechanism also cannot work since the charge carriers can hardly transmit into the floating gate due to the thick tunneling barrier layer of hexagonal Boron Nitride (h‐BN) and CIPS. The hysteresis (Figure 3b) is even smaller than the pure h‐BN device shown in Figure 3a.…”
Section: Figurementioning
confidence: 99%
“…transistors (BJT), [15][16][17][18] logic inverters, and memories, [3,5,[19][20][21] showing great potential in the future nanoelectronics. [6,[22][23][24][25][26][27] However, most of the reported studies can only achieve a single function on the same heterostructure. [8,28,29] Although there are several ways to realize multifunctional devices, [25,[30][31][32] including complex device architectural designs [3,33] and electrostatic gating, [2,34,35] these methods are timeconsuming, costly, and lack versatility.…”
Section: Introductionmentioning
confidence: 99%
“…van der Waals heterostructure electronic devices based on 2D materials have been investigated widely due to their unique properties, [ 1–11 ] such as rectifiers, [ 12–14 ] bipolar junction transistors (BJT), [ 15–18 ] logic inverters, and memories, [ 3,5,19–21 ] showing great potential in the future nanoelectronics. [ 6,22–27 ] However, most of the reported studies can only achieve a single function on the same heterostructure. [ 8,28,29 ] Although there are several ways to realize multifunctional devices, [ 25,30–32 ] including complex device architectural designs [ 3,33 ] and electrostatic gating, [ 2,34,35 ] these methods are time‐consuming, costly, and lack versatility.…”
Section: Introductionmentioning
confidence: 99%
“…In general, switching mechanisms of memories in three terminal devices are commonly based on carrier trapping at the gate insulator layer. Trapping phenomena are commonly due to processes including Fowler-Nordheim(FN) tunneling [38,39] or hot carrier injection. [40,41] Hence, to achieve high switching performance, including large memory windows and short transitions, high operating voltages are required to enhance these mechanisms.…”
Section: Resultsmentioning
confidence: 99%